1997
DOI: 10.1111/j.1439-037x.1997.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur and Micronutrient Nutrition of Groundnut in a Calcareous Soil

Abstract: Field experiments conducted on a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
5
15
1
Order By: Relevance
“…The synergistic effect of phosphorus and sulphur might be due to the utilization of more quantity of nutrients through their well-developed root system and nodules, which might have resulted in better growth and yield. These results confirm the earlier findings of Nagar et al (1993) in soybean, Sinha et al (1995) in winter maize, Choudhary and Das (1996) in black gram, Shankaralingappa et al (1999) in cowpea, Randhawa and Arora (2000) in wheat, Teotia et al (2000) in moong bean, Kumawat et al (2004) in taramira and Islam et al (2006) in rice. Aulakh et al (1990) and Singh et al (1995) have shown that the nature of phosphorus and sulphur interaction depends on their rates of application.…”
Section: Effect Of Phosphorus and Sulphur Application On 100 Seed Weisupporting
confidence: 90%
See 1 more Smart Citation
“…The synergistic effect of phosphorus and sulphur might be due to the utilization of more quantity of nutrients through their well-developed root system and nodules, which might have resulted in better growth and yield. These results confirm the earlier findings of Nagar et al (1993) in soybean, Sinha et al (1995) in winter maize, Choudhary and Das (1996) in black gram, Shankaralingappa et al (1999) in cowpea, Randhawa and Arora (2000) in wheat, Teotia et al (2000) in moong bean, Kumawat et al (2004) in taramira and Islam et al (2006) in rice. Aulakh et al (1990) and Singh et al (1995) have shown that the nature of phosphorus and sulphur interaction depends on their rates of application.…”
Section: Effect Of Phosphorus and Sulphur Application On 100 Seed Weisupporting
confidence: 90%
“…Black gram also responds well to sulphur fertilization especially in sulphur deficient soils since it has profound influence on protein synthesis and is a part of amino acids such as cystein, cystine and methionine. The sulphur deficiency has been widely observed in large areas especially in light textured soils low in organic matter due to the use of sulphur free fertilizers like urea and diammonium phosphate (Sinha et al, 1995). Available sulphur in soils of Jammu region ranges between 2.42 and 5.1 mg kg -1 , which is below the critical limit (Kour et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, P application had no effects on Car concentration under any water treatment. Our results support those found in other studies (Sharma , Sinha et al ), but they are in contradiction with other results found with different severities and durations of water deficit conditions (Zhang and Kirkham , Campbell and Sage , Singh et al ).…”
Section: Discussioncontrasting
confidence: 62%
“…Sharma (1995) also observed a higher photosynthetic rate and chlorophyll content in P-applied as compared to control mulberry plants. Sinha et al (1995) found that under adequate moisture levels, P application increased chlorophyll level due to an increase in the synthesis of chlorophyll a and b.…”
Section: Discussionmentioning
confidence: 97%